The Interconnection of Investor Cognition, Financial Literacy, and Neuroplasticity in Shaping Investment Choices in Nepal: A Study of Nepalese Investors - Gupta, Kumari Anjali (Apex Journal of Business and Management, 2026)
This study examines the impact of investor cognition and financial literacy on neuroplasticity among Nepalese investors, with risk absorption capacity considered as a mediating variable in Nepal’s capital market. Using a quantitative, cross-sectional design, primary data were collected from 300 individual stock market investors in Nepal and analyzed using SPSS through descriptive statistics, correlation, regression, and mediation analyses, with reliability confirmed using Cronbach’s Alpha. The findings reveal that investor cognition and financial literacy have a significant positive effect on neuroplasticity, indicating that greater cognitive awareness and financial knowledge enhance adaptive learning and flexibility in investment decision-making. Additionally, risk absorption capacity partially mediates the relationships between investor cognition and neuroplasticity and between financial literacy and neuroplasticity, highlighting the importance of risk-handling ability in transforming knowledge into adaptive investment behavior. The study contributes to behavioral finance literature by integrating cognition, financial literacy, and neuroplasticity within an emerging market context and offers practical implications for strengthening investor education, risk management, and cognitive resilience in Nepal’s capital market.